C. B. Wilbur correspondence - Wilbur, C. B.
TLS from Wilbur to Don Coppinger regarding the book and film based on her treatment of "Sybil," who suffered from multiple personality disorder.
Psychiatrist. Full name: Cornelia Burwell Wilbur. Born 1908; died 1992.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Coppinger, Don -- Correspondence; Multiple personality; Psychiatrists